Sistem Aplikasi Dan Pengerjaan Order Pada PT Telkom Akses Malang Divisi Drafter Dan SDI (Survey Drawing Inventory) - Nadhiva Auliya Fatmala; Nurul Azizah (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
With many requests for new network installations and the occurrence of network problems from customers, it is necessary to optimize applications and performance related to time-to-delivery orders to ensure that the goals set are achieved. Managers and leaders have so far supervised the performance of time-to-delivery orders by asking the Division Drafter and Survey Drawing Inventory (SDI), which form the basis for network development in Telkom. The work process carried out by the Survey Unit consists of surveying customers, determining points for the nearest network, marking paths, and designing files using the Google Earth application. The Survey Unit also has its task, making a RAB (building budget plan), which is useful for construction by technicians. The purpose of this study was to design and build a web-based order monitoring information system in PT Telkom Akses Malang Division Drafter and Survey Drawing Inventory (SDI). The system development method used is RAD (rapid application development). To find out the deficiencies of the existing system, PIECES analysis is used. The result of this research is a Monitoring and Evaluation Information System that can provide information about daily order performance to managers and leaders in PT Telkom Akses Malang Division Drafter and Survey Drawing Inventory (SDI).